Proceso de atención de enfermería en pacientes adolescentes con hemorragia postparto atendidas en el Hospital Sagrado Corazón de Jesús. período mayo – septiembre 2022 - Escobar Mullo, Samira Lindey (2022)
ABSTRACT Pregnancy in adolescents represents a risk to the life of the pregnant woman and the fetus, due to the lack of maturity of her body to face the development of a fetus in her uterus, exposing her to suffer various complications such as postpartum hemorrhage, therefore that the nursing staff must have sufficient knowledge of the PAE to provide the best care to these patients; Based on this need, the research team set itself the objective. "Apply a nursing care process in adolescent patients with postpartum hemorrhage treated at the Sacred Heart of Jesus Hospital". Developing for this a quantitative, descriptive, field investigation, of non- experimental design, where 39 postpartum adolescent patients participated, we reviewed 12 medical records of adolescent patients who had presented postpartum hemorrhage and 9 nursing professionals, to whom were applied as techniques to collect information, the assessment guide according to Virginia Henderson's 14 needs and the clinical history observation guide. Throwing as a result that: 50% of adolescents were under 17 years old, 67% high school studies, 25% had 5 prenatal check-ups; 92% had anemia; 17% were multiparous; 42% presented uterine atony; 25% tear; 50% episiotomy; 85% never had breathing difficulties; 72% ate 5 times a day; 92% had no problems moving; 90% sweated excessively; 82% drank aromatic drinks to improve their health. Concluding: based on the results obtained, a nursing care process was developed for adolescent patients with postpartum hemorrhage. Keywords: postpartum hemorrhage, adolescent pregnancy, nursing care process.